Communication in a Multicultural Virtual Environment for Modern Slovak Students - Hedviga Tkáčová; Roman Králik (Peoples' Friendship University of Russia (RUDN University), 2021)
The necessity of establishing intercultural communication skills in children and young people is growing in the modern world. Expanding, extending the openness and accessibility of the Internet area, where diverse people with varied ideas, interests, and aspirations meet, plays a significant role in this process. Todays youth are aptly referred to as digital aborigines, as they navigate the multicultural internet environment with ease, actively using modern technology that have already become a part of their daily lives. The goal of this study is to investigate the setting of an online multicultural environment from the perspective of Slovak university students, as well as to identify and analyze current problems that university students can see in online discussions about other cultures. A structured interview was used as the primary research approach. The results provide Slovak students perspective on the six most common topics that resonate in connection with different cultures on the current Internet: (1) concerns about ones own safety due to differences of others; (2) misinformation on the Internet regarding the difference of others; (3) cognitive prejudice; (4) religious prejudices; (5) exaggeration; and (6) influencing audience emotions. This paper holds the view that modern young people should develop not only the ability to navigate in virtual reality, but also make daily personal efforts to overcome personal barriers and develop intercultural media literacy, which the authors define as the ability to acquire, in addition to digital competencies, intercultural understanding skills and apply these skills in practice in the process of communication in the Internet environment.